Dent's disease complicated by nephrotic syndrome: A case report - He, Guohua (Intractable Rare Dis Res, 2016)
Dent's disease is an X-linked recessive proximal tubular disorder that mostly affects male patients in childhood or early adult life. The condition is caused by mutations in the CLCN5 (Dent disease 1) or OCRL (Dent disease 2) genes located on chromosome Xp11.22 and Xq25, respectively. In most male patients, proteinuria is subnephrotic but may reach nephrotic levels. Here, we report the first case of Dent's disease complicated by nephrotic syndrome. Dent's disease should be considered in the differential diagnosis of nephrotic syndrome, and especially in male patients with early onset of nephrotic syndrome. A urinary α1-microglobulin/albumin ratio > 1 may provide the first clue to a tubulopathy.